Revision of genera Quadraticossus, Martynovocossus and Fletcheriana (Insecta, Hemiptera) from the Middle Jurassic of China with description of a new species - Wang, Ying; Wang, Lin; Ren, Dong (Zootaxa, 2008)
Four species, belonging to three known genera of Palaeontinidae (Hemiptera), are described from the Middle Jurassic of Daohugou Village, Inner Mongolia, China. They are Quadraticossus eumorphus sp. nov., Q. fangi Wang & Ren, 2007, Martynovocossus punctulosus (Wang & Ren, 2006) Wang & Zhang, 2008 and Fletcheriana colorata Wang et al, 2006. Based on these materials, a new species is erected; line drawing of hind wing of Q. fangi is reconstructed and the diagnoses of the genera Quadraticossus Wang & Ren, 2007, Martynovocossus (Martynov, 1931) Wang & Zhang, 2008 and Fletcheriana Evans, 1956 are revised.